CHARACTERISTIC EVALUATION OF EBARA EZ 200 PUMP - EKA PUTRA (NIM : 13104151); Pimbimbing Utama : Ir. Arianto Santoso, M.Sc, WIDI
Nowadays, pump usage increases, so in selecting a pump, the performance characteristic shall be accurately considered and analyzed. To get the real performance characteristic of a pump, the pump shall be laboratory tested. In this final project, an Ebara pump of EZ 200 series is tested in laboratory. The pump is a pump of horizontal radial flow, volute, end suction, and closed impeller type. The pump is tested in constant pump shaft speed at varried flow rate. The shaft speed variation is obtained by combination of pulley dimension. The shaft speed is set at 1270 RPM, 1450 RPM, 1650 RPM, dan 2900 RPM. The variation of flow rate obtained by variation the gate valve opening at pump exit pipeline about 0, 1/8, 2/8, 3/8, 4/8, 5/8, 6/8, 7/8, dan 8/8. The test result shows the best efficiency point is at shaft speed about 1450 RPM and valve opening about 2/8, with flow rate about 0,0056 m3/s. From the cavitation analysis obtained NPSH available at pump test installation about 6,88 m, and NPSH required about 2,96 m. From the velocity triangle analysis at the best efficiency point, it is obtained that the theoretical head is about 17,25 m, and actual head from test result is about 13,48 m.